Bile salt (glycochenodeoxycholate acid) induces cell survival and chemoresistance in hepatocellular carcinoma. Issue 7 (12th December 2018) - Wang, Chengzhi; Yang, Manyi; Zhao, Jinfeng; Li, Xia; Xiao, Xiangcheng; Zhang, Yang; Jin, Xin; Liao, Mingmei
Abstract: Objective: Glycochenodeoxycholate acid (GCDA) is a toxic component in bile salts. It plays an important role in the development and progression of liver cancer. In this study, we investigated the underlying mechanism of GCDA in hepatocarcinogenesis and chemotherapy resistance. Materials and Methods: Cell proliferation was measured by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide (MTT) assay and clonality by Ki‐67 and colony‐formation assay. Apoptosis was examined by flow cytometry. Real‐time polymerase chain reaction (PCR) and western blot analysis were used to measure messenger RNA and protein levels, respectively. Short hairpin RNA was used to silence signal transducer and activator of transcription 3 (Stat3) expression. Results: Bile salts (GCDA) promoted the proliferation of hepatocellular carcinoma (HCC) cells (HepG2 and QGY‐7703), and GCDA treatment reduced the chemosensitivity of 5‐fluorouracil (5FU) in HepG2 and QGY‐7703 cells. GCDA upregulated the expression of antiapoptosis proteins Mcl‐1/Survivin/Bcl‐2. GCDA had no discernible effect on basal protein level or subcellular localization of phosphorylated Stat3. 5FU increased the apoptosis of HepG2 cells with silenced Stat3 expression, but GCDA‐induced chemoresistance was not reversed. Conclusions: GCDA‐reduced HCC cell chemosensitivity may occur by upregulating antiapoptosis proteins Mcl‐1/Survivin/Bcl‐2. Stat3 may be a target for enhancing the chemosensitivity of hepatocellular carcinoma cells, but GCDA‐induced chemoresistance is independent of Stat3. Abstract : Our findings provide strong evidence that GCDA is an agonist for the survival of hepatocellular carcinoma (HCC) cells by promoting cell proliferation and activating antiapoptotic genes (Mcl‐1/Survivin/Bcl‐2) to protect neoplasm cells against apoptosis. Stat3 is involved in chemoresistance of HCC but is independent of GCDA‐induced chemoresistance.